(untitled) (Journal of Mathematical Study, 2022)
In this paper, we introduce and study s-sequence-covering mappings and 1-s-sequence-covering mappings, obtain some characterizations of s-sequence-covering and compact images of metric spaces, and prove that every s-sequence-covering and compact mapping in first-countable spaces is a 1-s-sequence-covering mapping.